"Trade vs. grant dependency" and social enterprise performance: A mediating role of learning orientation. Issue 1 (2nd January 2022) - Bhattarai, Charan; Bhandari, Min
ABSTRACT: Pursuit of dual social and economic missions has created complicated dilemmas for social enterprises that whether they should rely more on nonprofit (e.g., grant dependency) or for-profit (e.g., trade dependency) strategies. Utilizing a sample of 164 UK social enterprises, this study found that relative to grant dependency, trade dependency has a more substantial positive direct effect on social performance. However, it has a more substantial positive indirect effect via learning orientation on economic and social performances. Therefore, this study concludes that social enterprise managers should prefer trade dependency to grant dependency to improve social performance. Nevertheless, they must promote and enhance learning culture and values (i.e., learning orientation) to concurrently improve, or at least not to deteriorate, their social enterprises' economic performance. The findings of this study are crucial for policymakers as well to develop and implement policies and programs to support social enterprises.